Empowerment of Digital Literacy for Youth of Karang Taruna Jerukgulung Village, Balerejo District, Madiun Regency Towards a Generation That is Technologically Capable and Wise in Social Media - Muchlis, Ibnu (Civiliza Publishing, 2025)
The purpose of this community service program is to improve the digital literacy capacity of the youth of Karang Taruna (Youth Organization) in Jerukgulung Village through the ABCD approach, enabling them to become a technologically savvy and social media-savvy generation. This community service program utilizes an Asset-Based Community Development (ABCD) approach to empower the youth of Karang Taruna in Jerukgulung Village to become a technologically savvy and social media-savvy generation. Activities included problem identification, asset mapping, formulating shared goals, action planning, technical training, and evaluation and follow-up. As a result, participants were able to manage social media productively, produce positive content based on local culture, and become agents of digital literacy education in the village. This community service program explored local potential, such as individual skills, digital devices, and village culture. Participants formulated a shared dream to make Karang Taruna a pioneer of digital literacy, a producer of positive content, and an agent of healthy social media education. They then designed and implemented programs through technical training, content production, and the launch of an official Instagram account. As a result, participants demonstrated improved digital skills, self-confidence, and a commitment to continue the digital literacy movement independently.